D8 Open Data for Agriculture Presentation by Perri Al-Riffai, IFPRI - Al-Riffai, Perrihan (2013)
Presentation by Perri Al-Riffai, IFPRI at the D8 Open Data for Agriculture Side event at IFPRI on May 1, 2013.